ANALYSIS OF INFORMATION TECHNOLOGY GOVERNANCE TO IMPROVE THE PERFORMANCE OF SEMARANG DISTRICT POPULATION AND CIVIL RECORDS SERVICES USING COBIT 2019 FRAMEWORK - Mahardika, Adrian Wisnu; Papilaya, Frederik Samuel (Jurnal Mnemonic, 2024)
This research aims to analyze Information Technology (IT) governance implemented in the Semarang Regency Population and Civil Registry Service (Disdukcapil) with the aim of improving service performance. The research method used is a case study using the COBIT 2019 Framework as an analysis guide. Data was collected through in-depth interviews, observation and documentation studies. The research results show that the adoption of the 2019 COBIT Framework in the IT governance of the Semarang Regency Dukcapil Disdukcapil is still not optimal. Several weaknesses in the IT management process were identified that hampered service performance. The implication of this research is the need to increase the understanding and application of COBIT 2019 in the IT governance of the Semarang Regency Dukcapil Disdukcapil in order to improve the IT management process and overall improve the quality of services provided to the community.